2015
DOI: 10.1007/s00436-015-4651-4
|View full text |Cite
|
Sign up to set email alerts
|

Additional information about tick parasitism in Passeriformes birds in an Atlantic Forest in southeastern Brazil

Abstract: The habits of birds make them more or less susceptible to parasitism by certain tick species. Therefore, while some bird species are typically found to be intensely infested, others are relatively unaffected. This study investigated the occurrence of ticks in Passeriformes inhabiting an Atlantic Forest fragment in southeastern Brazil, during the dry and rainy seasons, by means of parasitological indexes and multiple correspondence analysis, to determine the factors that influence tick parasitism in these birds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…It is known that humans can be parasitized by adults of A. ovale and A. aureolatum, but at a very low intensity, generally, by only one tick (Barbieri et al, 2014;Saraiva et al, 2014). However, large infestations of these ticks do occur in dogs (Guglielmone et al, 2003a;Ogrzewalska et al, 2012;Martins et al, 2012;Maturano et al, 2015). In this study, more than 30 individuals of A. ovale were collected from a single dog in Area 1.…”
Section: Discussionmentioning
confidence: 87%
“…It is known that humans can be parasitized by adults of A. ovale and A. aureolatum, but at a very low intensity, generally, by only one tick (Barbieri et al, 2014;Saraiva et al, 2014). However, large infestations of these ticks do occur in dogs (Guglielmone et al, 2003a;Ogrzewalska et al, 2012;Martins et al, 2012;Maturano et al, 2015). In this study, more than 30 individuals of A. ovale were collected from a single dog in Area 1.…”
Section: Discussionmentioning
confidence: 87%
“…Our estimation of bird species richness served as a proxy of the true richness of bird communities, but it may be influenced by different bird capture methods used in each study (de Angeli et al 2021 ). In the case studies reviewed, we observed that lower bird infestation by Amblyomma ticks occurred in localities with the highest bird species richness (Ogrzewalska et al 2008 ; Maturano et al 2015 ; Martinez-Sanchez et al 2020 ). Consequently, bird species richness appears to be a determinant of bird infestation in the Americas, which can be affected by habitat disturbance and can lead to changes in infestation patterns (Estades and Temple 1999 ; Ehlers Smith et al 2015 ).…”
Section: Discussionmentioning
confidence: 89%
“…The juvenile tick A. geoemydae population is abundant in soil and vegetational zone during the summer season, so they easily reach the preferred host, Chelonia, Squamata. In the absence of a favourable host, they can survive in new hosts under the same group, such as Coraciiformes (Martínez-Sánchez et al 2020 ) and Carnivora, and few on Galliformes (Rassouli et al 2016 ), Ciconiiformes (Labruna et al 2007 ), Passeriformes, Lagomorpha (Saraiva et al 2012 ), and Artiodactyla (Maturano et al 2015 ). The immature chelonian tick Amblyomma marmoreum infest on tortoises (Allan et al 1998 ).…”
Section: Discussionmentioning
confidence: 99%